The Effect Of Company Size, Profitability And Audit Opinion On Audit Delay (Empirical Study on Manufacturing Companies Listed on the IDX in 2021-2023) - Wibisana, Rangga; Rahman, Erpi; Krisdina, Tiana Fenny (LPPM Universitas Sebelas April, 2025)
In this study, the researcher discusses how much an impact a corporate entity that is late in reporting its financial statements to the public by using many measurement tools to further deepen the research conducted by the researcher, namely by using measurements such as company size, profitability (ROA, ROE, NPM and GPM), and audit opinions, this research method uses a quantitative method by searching for data and measuring data in the report financial data that has been published on IDX (Indonesia Stock Exchange) With the calculation of this data, we will find out how much influence the variables have on audit delays. This research will be very helpful for stakeholders such as managers, the community, investors and the government.